2014
DOI: 10.1186/1471-2334-14-182
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Production of recombinant Entamoeba histolyticapyruvate phosphate dikinase and its application in a lateral flow dipstick test for amoebic liver abscess

Abstract: BackgroundAmoebic liver abscess (ALA) is the most common clinical manifestation of extraintestinal amoebiasis especially in developing countries, causing up to 100 000 fatal cases annually. Accurate and early diagnosis is important to prevent the disease complications, however its diagnosis still poses many challenges due to the limitations of the available detection tools. Pyruvate phosphate dikinase (PPDK), an excretory-secretory protein of E. histolytica, has been reported as a potential diagnostic marker f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 24 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…The E. histolytica Gal/Gal-NAc lectin antigen is being utilized in commercial antigen detection tests such as the TechLab E. histolytica II ELISA (TechLab Inc). A study on ES proteins showed the diagnostic potential of pyruvate phosphate dikinase (PPDK), and its recombinant form has been used to develop a lateral flow dipstick test [15, 16]. In terms of treatment, auronofin has been identified as an effective drug which targets thioredoxin reductase, an ES protein of E. histolytica [17].…”
Section: Introductionmentioning
confidence: 99%
“…The E. histolytica Gal/Gal-NAc lectin antigen is being utilized in commercial antigen detection tests such as the TechLab E. histolytica II ELISA (TechLab Inc). A study on ES proteins showed the diagnostic potential of pyruvate phosphate dikinase (PPDK), and its recombinant form has been used to develop a lateral flow dipstick test [15, 16]. In terms of treatment, auronofin has been identified as an effective drug which targets thioredoxin reductase, an ES protein of E. histolytica [17].…”
Section: Introductionmentioning
confidence: 99%
“…Thus similar observation may be expected ESA. Western blot analysis using patients serum samples revealed the high diagnostic value of native and recombinant forms of PPDK for detection of ALA [16,17]. Since PPDK is a component of E. histolytica ESA, it is conceivable that it may be also useful as a target for detection of this parasite in stool sample.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant PPDK (rPPDK) protein was expressed and purified according to our previous report [16]. Meanwhile E. histolytica excretory-secretory antigens (EhESA) was produced using the method we have described earlier [17].…”
Section: Production and Purification Of Polyclonal Antibodiesmentioning
confidence: 99%
“…This procedure was similar to our previous report on a dipstick test for the detection of extraintestinal amoebiasis. 25 AgB, as the test line, was jetted linearly onto a Hi-Flow Plus 90 Membrane Card (Millipore, Billerica, MA) using an IsoFlow Dispenser (Imagene Technology, Hanover, NH). Various AgB concentrations (1, 1.2, 1.5, and 2 mg/mL) were dispensed onto separate membrane cards.…”
Section: Methodsmentioning
confidence: 99%